(untitled) (Economics and region, 2024)
The article assesses the current state of Ukraine’s construction industry using various methods of strategic analysis, such as PEST Analysis, SWOT Analysis, Five Forces Analysis, Stakeholder Analysis, Value Chain Analysis, and Scenario Planning. It provides an overview of the current situation in Ukraine’s construction industry over the past years. The identified problems include: decreased investments in the construction industry; outdated technologies and equipment; shortage of skilled labor; unsatisfactory quality of construction materials and works; disruptions in technological chains and provision of Ukraine’s material and technical base: improvement of legislation and regulatory environment, especially in the field of construction safety and energy efficiency; development of partnerships with international financial companies to attract investments and modern technologies; implementation of advanced technologies in construction to reduce costs and improve quality; development of infrastructure necessary for construction; improvement of the system for training specialists; support for Ukrainian manufacturers of construction materials.